Duplication of gallbladder: a rare anomaly of biliary tract- A case report - Tahira Hameed; Rizwan Aziz; Munazzah Aziz (Journal of the Pakistan Medical Association, 2023)
Incomplete duplication of gall bladder or vesica fellea divisa is one of the rare anomalies of gallbladder. Until now, 25 cases have been reported; of which four were proceeded with laparoscopic cholecystectomy. In our case, we diagnosed this nadir anomaly laparoscopically, posing a technical challenge since no radiological clue was observed beforehand. Successful laparoscopic resection of duplicated gall bladders was performed followed by Magnetic Resonance CholangioPancreaticography. Keywords: Gallbladder, laparoscopy, anomaly.